Subperiosteal injections during facial soft tissue filler injections—Is it possible?. (16th July 2019) - Pavicic, Tatjana; Yankova, Mariya; Schenck, Thilo L.; Frank, Konstantin; Freytag, David L.; Sykes, Jonathan; Green, Jeremy B.; Hamade, Hassan; Casabona, Gabriela; Cotofana, Sebastian
Abstract: Background: It can be hypothesized that safety during soft tissue filler injection could be enhanced if the product could be positioned between the periosteum and the bone surface i.e. subperiosteal. Aim: This study investigated the feasibilityof subperiosteal injections. Patients/Methods: We analysed 126 injection procedures performed in seven Caucasian body donors (4 males, 3 females) with a mean age of 75.29 ± 4.95 years [range: 70 – 87] and a mean body mass index of 23.53 ± 3.96 kg/m 2 [range: 16.46 – 32.23]. The injection procedures were performed in the forehead, scalp, zygomatic arch and the mandible bilaterally. Injection procedures were conducted using 25G, 27G and 30G sharp‐tip needles (TSK Laboratory, Tochigi, Japan) and at various angles from the bone surface measured with a goniometer: 90 degrees (perpendicular), 45 degrees and 10 degrees (as tangential as possible to bone surface). Results: Cadaveric dissections of the injection sites showed that no product was located deep to the periosteum in any of the investigated regions. This indicates that all performed injection procedures positioned the product superficial to the periosteum (100%) with a zero‐success rate of subperiosteal injections. Conclusion: In the setting of this cadaveric investigation, despite varying needle size and injection angle, subperiosteal injection could not be achieved. This indicates that the product can spread uncontrolled into more superficial layers yielding an increased risk for adverse aesthetic and vascular events.